2021
DOI: 10.1002/elps.202100003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic reconstruction and phylogenetic analysis by 193 Y‐SNPs and 27 Y‐STRs in a Chinese Yi ethnic group

Abstract: Yi is the seventh‐largest ethnic group in China and features mountainous regional characteristics. The Liangshan Yi Autonomous Prefecture is the largest Yi agglomeration with isolated geographical conditions, profoundly impeding genetic communication. Here, we investigated 427 unrelated males of Liangshan from 193 Y‐chromosome single nucleotide polymorphisms (Y‐SNPs) and 27 Y‐chromosome short tandem repeats (Y‐STRs) to reveal the genetic structure and paternal phylogeny of the group. The haplogroup diversity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…It was also the group of Enthaler that observed a ring‐closing C−O bond metathesis from polytetrahydrofuran (Figure 1b) [9] . Harsh reaction conditions and the continuous removal of THF through distillation limited this process to the less prevalent polytetrahydrofuran [10] . In 2018, Morandi et al.…”
Section: Figurementioning
confidence: 99%
“…It was also the group of Enthaler that observed a ring‐closing C−O bond metathesis from polytetrahydrofuran (Figure 1b) [9] . Harsh reaction conditions and the continuous removal of THF through distillation limited this process to the less prevalent polytetrahydrofuran [10] . In 2018, Morandi et al.…”
Section: Figurementioning
confidence: 99%
“…Hard Lewis acid, AlCl 3 was then introduced into the IOD‐containing electrolyte to promote the release of iodine and the ring‐opening of IOD (Figure S1b, Supporting Information). [ 31 ] The reversibility of IOD/AlCl 3 ‐containing electrolyte was confirmed under O 2 atmospheres. The oxidation peak of cells with IOD/AlCl 3 ‐containing electrolyte located at ≈3.85 V, which is similar to that of LiI‐containing batteries, indicating that with the addition of AlCl 3 , the oxidation of iodine species (3II3+2e$3{{\mathrm{I}}}^ - \to {\mathrm{I}}_3^ - + 2{{\mathrm{e}}}^ - $) occurred ( Figure ).…”
Section: Resultsmentioning
confidence: 97%
“…Inclusion criteria were as follows: (1) containing at least the 27 Y-STR data information as the Y Filer Plus kit; (2) containing high-resolution Y-SNP information, not just under one of the major haplogroups; (3) data can be obtained from the attached table. A total of 3333 individuals were collected from five high-resolution Y-SNP-STR studies as shown in electronic supplementary material, table S1 [12][13][14][15][16]. To facilitate data analysis and statistics, we unified SNPs and STRs to a consistent level (electronic supplementary material, table S2).…”
Section: Samplesmentioning
confidence: 99%